ISSUES OF EQUIVALENCE IN SIMULTANEOUS AND WRITTEN TRANSLATION - Qodirova , Nodira Baxram qizi (Innovative Development in Educational Activities, 2023)
Equivalence in translation requires a deep understanding of both target and source languages’ customs and culture and differs within simultaneous and written translation styles accordingly. This article is devoted to the issues of equivalence in simultaneous and written translation.